Assessment of body conformation, feed efficiency and morphological characteristics in Rhode Island Red-White strain chicken - DAS, ANANTA KUMAR; KUMAR, SANJEEV; RAHIM, ABDUL; KOKATE, LAXIKANT SAMBHAJI; MISHRA, ANIL KUMAR (The Indian Journal of Animal Sciences, 2014)
This investigation aimed to assess body conformation, feed efficiency and morphological characteristics in RIR-White strain chicken of which 73 single hatched chicks were investigated at CARI, Izatnagar. Data were analyzed by least squares analysis of variance. Least squares (LS) means of chick weight, body weights at 4th, 6th, 8th, 12th and 16th weeks were estimated. Corresponding LS means of shank length, keel length and breast angle at 4th, 6th, 8th, 12th and 16th week of age, and of body weight gain, feed consumed and FCR were estimated. Sex had effect significant on body conformation traits and weight gain at the age of 8th week onwards and on FCR at 8th and 16th weeks. Phenotypic correlations among intra-week body conformation traits were positively high throughout the ages. Pattern within feather was self-white with normal feather morphology and solid white plumage, yellow skin and shank, and red single comb. The strain laid brown eggs. This might serve as strain characteristics of this rare strain of RIR chicken.